Vaccine Evolution and Its Application to Fight Modern Threats - Andreano, Emanuele; D'Oro, Ugo; Rappuoli, Rino; Finco, Oretta (Frontiers in Immunology, 2019)
Before the development of the first vaccine, infectious diseases were the major cause of deaths around the globe with life expectancy estimated to be less than 50 years. Three measures have helped to drastically reduced the burden of infectious diseases but only vaccines have proven to be able to eradicate infectious agents. Herein we describe new methodologies that have paved the way for what is currently conceived as modern vaccinology and the use of vaccines to tackle antimicrobial resistance, the biggest global threat of our days.